2018
DOI: 10.1128/mcb.00259-17
|View full text |Cite
|
Sign up to set email alerts
|

A Complex Relationship between Immunity and Metabolism in Drosophila Diet-Induced Insulin Resistance

Abstract: Systemic and tissue-specific insulin resistance have been described in , and are accompanied by many indicators of metabolic disease. The downstream mediators of insulin-resistant pathophysiology remain unclear. We analyzed insulin signaling in the fat body using loss- and gain-of-function. When expression of the sole Insulin receptor (InR) was reduced in larval fat bodies, animals exhibited developmental delay and reduced size in a diet-dependent manner. Fat body InR knockdown also led to reduced survival on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(92 citation statements)
references
References 91 publications
9
83
0
Order By: Relevance
“…) gene enrichment together is also in agreement with the well‐established relationship between intestinal bacteria and metabolism in diverse species including fly . As TAG levels were found altered in several of the above metabolic studies , are associated with cold tolerance in D. melanogaster , and, notably, show alterations in the offspring of cold‐exposed mice , we identified altered TAG regulation as a potential trait that might be inherited following cold exposure.…”
Section: Resultssupporting
confidence: 86%
“…) gene enrichment together is also in agreement with the well‐established relationship between intestinal bacteria and metabolism in diverse species including fly . As TAG levels were found altered in several of the above metabolic studies , are associated with cold tolerance in D. melanogaster , and, notably, show alterations in the offspring of cold‐exposed mice , we identified altered TAG regulation as a potential trait that might be inherited following cold exposure.…”
Section: Resultssupporting
confidence: 86%
“…At present, we know little about cell-specific aspects of IMD activity in the midgut. For example, several lines of evidence implicate IMD in metabolic homeostasis (17,(51)(52)(53). However, we don't know if these immunemetabolic links are cell-intrinsic, or if they are secondary to IMD-mediated changes to the gut microbiota, with attendant shifts in microbial control of metabolism in the host.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, several studies identified interaction points between immune and insulin responses in the fly. For example, depletion of the insulin receptor from the fat body alters the expression of immune response genes, and alters sensitivity to infection (Musselman et al, 2017). Furthermore, mutations of the IRS homolog chico increase survival after infection with Pseudomonas aeruginosa and Enterococcus faecalis (Libert et al, 2008); challenges with Mycobacterium marinum lower AKT phosphorylation, and diminish systemic insulin activity (Dionne et al, 2006); activation of TOR blocks AMP expression (Varma et al, 2014); infection increases expression of the FOXO-responsive transcript 4E-BP ortholog thor (Bernal and Kimbrell, 2000); and FOXO regulates the expression of intestinal antimicrobial peptides (Becker et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest broad tissue autonomy in IMD responses. In contrast, 29.8% of genes affected by IMD activation are also affected by loss of the insulin receptor in fat tissue (Musselman et al, 2017) (Figure 4D, E). The overlap between the two gene sets includes genes required for fatty acid beta-oxidation, carbohydrate metabolism, and the TCA cycle.…”
Section: Activation Of Imd In the Fat Body Modifies Metabolismmentioning
confidence: 96%